Biocidal effects of a wipe-down procedure using common veterinary cleansers on microbial burden within working canine exterior coats - Perry, Erin B.; Discepolo, Dakota R.; Liang, Stephen Y.; Scott, Maurnice; Williamson, Kyleigh; Bender, Kelly S. (Frontiers in Veterinary Science, 2023)
Introduction: Recent work demonstrating reduction of aerosolized contamination via a wipe-down procedure using common veterinary antiseptics (1) offers promise regarding health concerns associated with cross-contamination from working canines to humans. While mechanical reduction can be achieved via a wipe-down procedure, the biocidal impact on flora within the exterior coat is unknown. Methodology: This study assessed the biocidal impact of antiseptics on the exterior bacterial community of the canine. Lint-free towels were saturated with 2% chlorhexidine gluconate scrub, or 7.5% povidone-iodine scrub diluted at a 1:4 ratio. Treatments were rotated across the dorsal aspect kennel housed fox hounds (n = 30). Sterile swabs were collected in triplicate prior to, and following wipe down, stored in Amies solution at 4ºC, plated onto nutrient agar and reduction in colony forming units (CFU) was measured across both treatments. Statistical analysis utilizing PROC GLM examined effects of treatment (P ≤ 0.05). Molecular analysis of the 16S rRNA gene was completed for 3 hounds. Results:Reduction in CFU was measured (P < 0.001) for both antiseptics. Qualitative molecular data indicated that both antiseptics had a biocidal effect on the dominant microbial community on the exterior coat with gram-positive, spore-forming CFU predominating post-treatment. Conclusion:Effective wipe-down strategies using common veterinary cleansers should be further investigated and incorporated to safeguard working canine health and prevent cross-contamination of human personnels.